Eric Voegelin’s New Political Philosophy: A Brief Overview (Economic and Political Thought, 2013)
The article shortly presents the silhouette and views of an Austrian-Americanpolitical philosopher Eric Voegelin, who is not well known in Poland.Voegelin radically questioned the methods and practices used in the modernsocial sciences. The great development of exact sciences in the time of scientificrevolution led to a belief that the methods used in those sciences can besuccessfully used in social sciences. In the course of time, the view eliminatedother methods and acknowledged experience, inductive concluding andmathematical logics as the only acceptable methods in scientific research.Positivism made the methods the only criteria of scholarship and all the fieldsthat did not use them were expelled from the area of science.According to Voegelin, science requires the use of such methods that areadequate to the nature of scientific examination (mathematics is for examplenot very useful in the analysis of The Republic by Plato). A man wantsto know but does not get to know the reality as an external observer but asa participant. A man gets to know some fragments of the reality not in anempiric way but through internal consciousness and meditation. The historyof humanity is a process of “attunement” of human cognition to the existingorder of existence. The consciousness of a transcendental source of existencehas always accompanied a man. Originally, a man finds a reflection of anexistence order in a cosmological civilization. A leap in being towards theexisting order takes place in Israel through revelation and finishes in Christianity.This makes a man give up a myth for the benefit of history. Scienceis to help in the attunement to the order of existence and its transcendentalsource.